2011
DOI: 10.4055/cios.2011.3.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyaluronic Acid-Carboxymethylcellulose Solution on Perineural Scar Formation after Sciatic Nerve Repair in Rats

Abstract: BackgroundScar tissue formation is the major cause of failure in peripheral nerve surgery. Use of a hyaluronic acid-carboxymethylcellulose (HA-CMC) membrane (Seprafilm) as a solid anti-adhesion barrier agent is one of the therapeutic approaches to reduce postoperative scar tissue formation. However, a solid membrane may not be suitable for repair of a weak peripheral nerve site. This study examined the effect of HA-CMC solution on perineural scar formation after peripheral nerve repair in rats.MethodsThe sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…In peripheral nerves, HA has positive effects on peripheral nerve regeneration modulating glial cell adhesion and migration and neuronal sprouting [15][16][17]. Yet, topical application of HA is able to reduce the scar formation and create a more favorable environment for nerve regeneration [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral nerves, HA has positive effects on peripheral nerve regeneration modulating glial cell adhesion and migration and neuronal sprouting [15][16][17]. Yet, topical application of HA is able to reduce the scar formation and create a more favorable environment for nerve regeneration [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, this author found better mean conduction velocities (MCVs) and faster functional recovery in HA-treated nerves (0.82 ± 0.08 m/s) compared with nerves treated with saline, in which the MCV was 0.76 ± 0.04 m/s (P < 0.05) [31]. Park et al found that topical application of HA carboxymethylcellulose solutions in rats significantly reduced nerve adherence score and the number of cellular components compared with the saline group (control group) (P < 0.05) [70]. The authors concluded that HA carboxymethylcellulose solutions improved nerve regeneration and reduced perineural scar formation and adhesion after sciatic nerve repair [70].…”
Section: Mechanisms Of Action Referencesmentioning
confidence: 99%
“…Use of the hyaluronic acid-carboxymethylcellulose membrane Seprafilm as a solid anti-adhesion barrier agent is one of the therapeutic approaches used to reduce postoperative scar formation and is effective in promoting peripheral nerve regeneration at the repair site [69]. In addition, HA-carboxymethylcellulose solutions improve nerve regeneration and reduce perineural scar formation and adhesion after sciatic nerve repair [70]. It has been confirmed that direct application of HA-carboxymethylcellulose in transected nerves may limit axonal outgrowth by contact with regenerating axons; therefore, HAcarboxymethylcellulose barriers may prove to be a tool to prevent neuroma formation through inhibiting axonal growth [71].…”
Section: Hyaluronic Acidmentioning
confidence: 99%
See 2 more Smart Citations